Defect modulated dielectric properties in powder aerosol deposited ceramic thick films - Eckstein, Udo; Khansur, Neamul Hayet; Urushihara, Daisuke; Asaka, Toru; Kakimoto, Ken ichi; Fey, Tobias; Webber, Kyle Grant (Ceramics International, 2022)
Powder aerosol deposited (PAD) ceramic thick films are a promising candidate for applications in energy storage and energy harvesting. The room-temperature deposition process allows for integration of ceramic films on low-melting substrates, such as stainless steel and polymers, without sintering. Despite this, the dielectric and electromechanical properties vastly differ from bulk ceramics due to internal residual stresses, oxygen defects, and the nano-grained microstructure associated with the deposition process. Although thermal annealing can improve macroscopic properties, precise control of the thermal expansion mismatch between the film and the substrate is required to avoid delamination and film cracking. In this study, we present a method to determine the actual thermal expansion of the film based on the fabrication of freestanding PAD films. Utilizing freestanding films, we demonstrate that dopants and processing conditions such as the carrier gas species directly influence oxygen defects thus modulating the unit cell volume and the conductivity of the oxide film. This is found to be crucial to attain improved dielectric properties within a moderate temperature environment (500 °C) preserving the benefits of the room-temperature deposition process. Additional densification mechanisms are investigated with transmission electron microscopy, scanning electron microscopy, and X-ray microtomography.
CRIS-Team Scopus Importer:2022-10-14
Keywords: Energy storage; Functional ceramic thick films; Powder aerosol deposition; Structural characterization